Study on Multi-objective Energy Storage Operation Chart of Mixed Reservoirs in Xijiang River Basin - JIANG Zhiqiang; FENG Zhongkai; QIN Hui; CHEN Lu; HUANG Mutao; ZHOU Jianzhong (Renmin Zhujiang)
For the current research on energy storage operation charts (ESOC) of reservoir groups,little attention has been paid to large-scale mixed reservoirs, and the coupling of multi-objective operation with ESOC has not been considered. In view of this, by improving the originaldiscriminant coefficient formula, water balance equation and energy storage calculation formula,this paper improves and expands the traditional ESOC model of pure cascade reservoirs, putsforward a new calculation method for the ESOC of large-scale mixed reservoirs, and establishes amulti-objective ESOC optimization model for mixed reservoirs based on a comprehensiveconsideration of flood control, power generation and ecological objectives. Taking Xijiang RiverBasin as an example, the multi-objective Pareto front of upstream reservoirs under differentminimum discharges is obtained, and the optimal multi-objective schemes under different powergeneration guarantee rates and different ecological flow satisfaction rates are extractedaccording to the actual requirements and constraints. The model and method presented in this papercan not only deal well with the complex water volume and water head relations in the drawing andsimulation of mixed reservoirs ESOC, but also effectively apply the obtained multi-objective ESOCto the actual operation.